PENGARUH PENERAPAN E-SAMSAT DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DENGAN KUALITAS PELAYANAN SEBAGAI VARIABEL MODERASI (STUDI PADA UPTD SAMSAT CIRUAS PERIODE 2020-2024) - Pramesti, Nur Fitri; Khodijah, Ina; Komarudin, Mochamad Fahru (Yayasan Education and Social Center, 2025)
One type of local tax that contributes significantly to local revenue is motor vehicle tax. This tax plays an important role as a source of revenue that supports the financing of various regional development programs and activities. In reality, most citizens still do not optimally fulfill their tax obligations, even though this is an inherent responsibility as citizens. This situation arises due to the low level of public compliance in fulfilling their tax payment obligations for the motor vehicles they own. The objective of this study is to analyze the impact of the implementation of e-samsat and tax penalties on the compliance rate of motor vehicle taxpayers, with service quality as a moderating variable at the UPTD Samsat Ciruas. This study was conducted using a quantitative approach. The study focused on taxpayers registered with the Ciruas Samsat UPTD, totaling 270,899. The Slovin formula was used to determine the sample size, resulting in 100 respondents. Respondents were selected using purposive sampling. Data analysis was conducted using the Structural Equation Modeling (SEM) approach, processed using SmartPLS 4.1.1.2. The implementation of e-samsat has an impact on the compliance of motor vehicle taxpayers. Tax penalties and service quality do not influence the compliance of motor vehicle taxpayers. Service quality cannot moderate the influence of the implementation of e-samsat and tax penalties on taxpayer compliance.